Sachiko : a novel - Endō, Shūsaku, 1923-1996 (Weatherhead books on Asia., 2020)
"In novels such as Silence, Endō Shūsaku examined the persecution of Japanese Christians in different historical eras. Sachiko, set in Nagasaki in the painful years between 1930 and 1945, is the story of two young people trying to find love during yet another period in which Japanese Christians were accused of disloyalty to their country. In the 1930s, two young Japanese Christians, Sachiko and Shūhei, are free to play with American children in their neighborhood. But life becomes increasingly difficult for them and other Christians after Japan launches wars of aggression. Meanwhile, a Polish Franciscan priest and former missionary in Nagasaki, Father Maximillian Kolbe, is arrested after returning to his homeland. Endō alternates scenes between Nagasaki-where the growing love between Sachiko and Shūhei is imperiled by mounting persecution-and Auschwitz, where the priest has been sent. Shūhei's dilemma deepens when he faces conscription into the Japanese military, conflicting with the Christian belief that killing is a sin. With the A-bomb attack on Nagasaki looming in the distance, Endō depicts ordinary people trying to live lives of faith in a wartime situation that renders daily life increasingly unbearable. Endō's compassion for his characters, reflecting their struggles to find and share love for others, makes Sachiko one of his most moving novels"--